S96 IFN-β dynamics during respiratory viral infection of macrophages: insights for therapeutic strategies. (December 2018) - Watson, A; Spalluto, M; McCrae, C; Cellura, D; Burke, H; Cuoosamy, D; Freeman, A; Hicks, A; Hühn, M; Ostridge, K; Staples, K; Vaarala, O; et al.
Abstract : Introduction and objectives: Viral infections are major drivers of exacerbations and clinical burden in patients with asthma and COPD. IFN-β is essential for controlling the infection and spread of viruses such as influenza. However, in recent clinical trials, treatment with IFN-β failed to prevent asthma exacerbations. We aimed to compare the utility of IFN-β as either a treatment or prophylactic for modulating influenza infection in macrophages from health and COPD, with an aim of generating new insights for the optimal design of future clinical trials. Methods: Monocyte-derived macrophages (MDM) and primary alveolar macrophages were isolated from healthy and COPD patients. Cells were then infected with influenza virus either prior to or after IFN-β stimulation. Levels of influenza infection were measured by%NP1 +cells using flow cytometry. Viral RNA shedding and anti-viral gene expression (Including OAS1, MX1 and RIG-I) were measured by qPCR. Concentration of inflammatory cytokines (including GM-CSF, TSLP, IL-33, IL-25, TNF-α, IL-1β, IL-6, CCL17, CCL22 and RANTES) in supernatants was measured using MSD. Results: Levels of influenza infection in MDMs was similar for both healthy and COPD patients with a%NP1 of 24.4 and 22.0, respectively (p=0.79). Treatment after infection of MDMs with IFN-β was ineffective at modulating influenza infection rates or viral load but IFN-β prophylaxis effectively reduced%NP1 + cells and shedding by 85% (p<0.001) and, 20 fold (p<0.01), respectively. The effect of IFN-β prophylaxis in modulating influenza infection lasted up to 1 week in MDMs from both health and COPD. This was mirrored by the expression of OAS1, MX1 and RIG-I interferon stimulated genes. Exogenous IFN-β did not induce inflammatory cytokine production by MDMs. Conclusions: We modelled IFN-β dynamics in vitro and highlight the potential for intermittent prophylactic doses of exogenous IFN-β to modulate viral infection. This generates novel insights to both understand recent clinical trial results in asthma and to aid the optimal design of future clinical trials in both asthma and COPD.